Digital technologies in personnel management - Makovoz, Oksana; Lysenko, Sergii (UKEY Consultancy & Publishing, 2024)
This paper examines the pivotal role of digital technologies in the transformation of personnel management within contemporary enterprises. As businesses increasingly emphasize efficiency, adaptability, and innovation, digitalization in human resources (HR) management is becoming indispensable. The integration of cutting-edge technologies such as Artificial Intelligence (AI), Big Data, Machine Learning (ML), the Internet of Things (IoT), and 5G within HR processes stands at the forefront of this transformation, enhancing productivity and fostering sustainable organizational development. The study focuses on several critical aspects of HR digital transformation including recruitment, employee development, performance evaluation, and engagement strategies. It systematically examines the impact of digital technologies on these HR functions and assesses how they contribute to creating a more effective work environment. The research underscores the potential of digital tools to not only streamline HR processes but also to enhance employee satisfaction and organizational efficiency. Empirical evidence from leading companies that have successfully integrated digital HR solutions suggests significant cost reductions and improved operational efficiency. The paper analyzes these cases to identify the benefits and challenges associated with HR digitalization. It further discusses the implications of these technologies on corporate culture and the overall workforce management. Ultimately, this article provides a comprehensive overview of the challenges and opportunities presented by HR digitalization. It offers insights into effective strategies for implementing digital transformations in HR processes, based on practical examples from industry leaders. The findings aim to assist organizations in making informed decisions about optimizing their HR operations through digital technologies, thereby enhancing their overall effectiveness and adaptability in the digital era.
Keywords: digitalization; organizational transformation; human resources management; artificial intelligence; big data; machine learning; internet of things; employee engagement